ANALISIS MANAJEMEN PIUTANG (STUDI KASUS PADA PT BALTEC EXHAUST DAN INLET SYSTEM INDONESIA) - Basalamah, Aisyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research aims to analyze account receivables management in PT Baltec Exhaust and Inlet System Indonesia. The discussion includes the management of account receivables, internal control of receivables, elements of billing in account receivables, and obstacle of account receivables billing. The data of this study are obtained from interviews with accounting and finance department manager of PT Baltec Exhaust and Inlet System Indonesia. The primary data of this studyare documents obtained from the company. The results of this research shows that the management of accounts receivable and the internal control of accounts receivable have been implemented well. However, the company has problems in tasks splitting in accounting and finance department. The company has not used any software to record their accounting. Other problems are that the works the company has made not match the work contract and that some customers are having financial difficulties that make billing slower. Keywords : account receivable management, internal control, service company.